Survival sex and trafficked women: The politics of re-presenting and speaking about others in anti-oppressive qualitative research. (May 2019) - Hardesty, Melissa; Gunn, Alana J
Qualitative research grounded in a social constructionist epistemology troubles the assumption, integral in positivist research, that a researcher can be neutral and apolitical. In fact, many scholars are drawn to constructionist epistemologies because they situate the research process as a site of ontological resistance and social change. This essay explores the politics of voice and representation in anti-oppressive qualitative research. Using an example from one author's research on stigma management among formerly incarcerated women, and the particularly pernicious stigma women faced if they had engaged in sex work, we detail the benefits and pitfalls of either re-presenting research participants in their exact words or changing participants' words, a process we refer to as re-languaging. Drawing upon philosophical and social scientific scholarship on the "crisis of representation" in qualitative research and recent scholarship and news articles about human sex trafficking, we underscore the powerful political effects of language. We argue that researchers' choices about language are neither inherently liberatory nor oppressive, but they are always political. We call for a more reflexive scholarly dialog on voice in qualitative social work research and press scholars to explicitly engage the question of whom and what we represent when we claim to represent marginalized others.